The moderating effect of privacy in the relationships between residential livability and residents' life satisfaction - Bashari, Sunusi; Hashim, Ahmad Hariza; Abu Samah, Asnarulkhadi; Ahmad, Nobaya (Universiti Sains Malaysia Press, 2021)
This article seeks to determine whether privacy has a moderating effect on the relationship between residential livability and life satisfaction among low-income groups in Dutse, Jigawa State, Nigeria. The study utilised a quantitative research design, whereby descriptive and inferential analyses were employed. This was achieved through a well-structured questionnaire administered to low-cost housing residents in the state. The data were subjected to descriptive analysis using the Statistical Package for Social Science (SPSS) software and structural equation modelling (SEM) using Analysis of Moment Structures (AMOS). The results indicated that about 73.4% of the residents experienced a low level of life satisfaction. The findings from the SEM showed that the moderating effect of privacy in the relationship between the dwelling unit and life satisfaction was good. Meanwhile, privacy was not a moderator in the relationship between social environment and life satisfaction. Finally, the article revealed that the residents' life satisfaction could be improved if dwelling unit features and privacy were considered in the low-cost housing design. Practically, the study serves as a blueprint for government policy in designing low-cost housing in the future.